Virtual supermarket setting: Exploring antecedents of emotions and purchase intentions - Loureiro, S. M. C.; Correia, C.; Guerreiro, J. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
Virtual Reality is based on three key characteristics: immersion, interactivity (Boyd & Koles, 2018). Firstly, when exposed to a virtual environment, the individual experiences the sense of immersion or presence within that environment. The user feels like being there and escaping or becoming isolated from the real world. Beside immersion, VR provides a very dynamic environment (Loureiro et al., 2019), which is important to create consumer involvement. Hence, the current study explores antecedents of emotions and purchase intention in virtual supermarket setting.